Respuesta :

Answer:

-3 units

Step-by-step explanation:

You can solve this problem using the equation [tex]rate = \frac{change}{time}[/tex].

First identify the change with the equation [tex]change= f_{final} - f_{initial}[/tex]. Since you are finding the rate of change from -1 to 1, the equation will be [tex]change = f(1)-f(-1)[/tex] which is 0-6 or -6.

Next, find the time, or in this case, change in x. This will be [tex]x_{final} -x_{initial}[/tex] or

1-(-1), which is 2.

Finally, plug it all in:

[tex]rate=\frac{-6}{2}=-3[/tex]